Luas Lahan dan Pemenuhan Kebutuhan Dasar (Kasus Rumah Tangga Petani Miskin di Daerah Dataran Rendah Kabupaten Seluma) - Bahrin Bahrin; Basita Ginting Sugihen; Djoko Susanto; Pang S Asngari (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluh Pertanian Indonesia), 2010)
The mayority of the poor farmers have relativity enough land, approximately 1 Ha per household. Their poverty is considered as relatively poor. There were four factors which make the poor farmers hardly overcome their problems, namely: working pattern which mostly rely on physical potency; low level of adoption of innovation; poverty trap bounding and low competence to manage opportunity and potency. The poor farmers have to be motivated to get involve in learning process. By doing this approachit is hoped that the farmers could change to get bette, more effective dan more productive in land use.Keyword: poor farmers, land, behavior, household’s needs